Exploring differences in individual and group judgements in standard setting. Issue 9 (2nd July 2019) - Yeates, Peter; Cope, Natalie; Luksaite, Eva; Hassell, Andrew; Dikomitis, Lisa
Abstract : Context: Standard setting is critically important to assessment decisions in medical education. Recent research has demonstrated variations between medical schools in the standards set for shared items. Despite the centrality of judgement to criterion‐referenced standard setting methods, little is known about the individual or group processes that underpin them. This study aimed to explore the operation and interaction of these processes in order to illuminate potential sources of variability. Methods: Using qualitative research, we purposively sampled across UK medical schools that set a low, medium or high standard on nationally shared items, collecting data by observation of graduation‐level standard‐setting meetings and semi‐structured interviews with standard‐setting judges. Data were analysed using thematic analysis based on the principles of grounded theory. Results: Standard setting occurred through the complex interaction of institutional context, judges' individual perspectives and group interactions. Schools' procedures, panel members and atmosphere produced unique contexts. Individual judges formed varied understandings of the clinical and technical features of each question, relating these to their differing (sometimes contradictory) conceptions of minimally competent students, by balancing information and making suppositions. Conceptions of minimal competence variously comprised: limited attendance; limited knowledge; poor knowledge application; emotional responses to questions; 'test‐savviness', or a strategic focus on safety. Judges experienced tensions trying to situate these abstract conceptions in reality, revealing uncertainty. Groups constructively revised scores through debate, sharing information and often constructing detailed clinical representations of cases. Groups frequently displayed conformity, illustrating a belief that outlying judges were likely to be incorrect. Less frequently, judges resisted change, using emphatic language, bargaining or, rarely, 'polarisation' to influence colleagues. Conclusions: Despite careful conduct through well‐established procedures, standard setting is judgementally complex and involves uncertainty. Understanding whether or how these varied processes produce the previously observed variations in outcomes may offer routes to enhance equivalence of criterion‐referenced standards. Abstract : How does variability arise when different groups decide upon the appropriate cut score for an examination? The authors shine light on this question by exploring the complex interaction between individual and group processes.